2013
DOI: 10.5120/10137-4279
|View full text |Cite
|
Sign up to set email alerts
|

Review: Robot Devices for Gait Rehabilitation

Abstract: The main motivation of gait rehabilitation is to help a patient recovering from injury, illness or disease, to recover some locomotor abilities in order to promote as much independence as possible in activities of daily living tasks, and to assist the patient in compensating for deficits that cannot be treated medically. However, the amount of hands-on therapy that patients can receive is limited, as economic pressures are inherent in the health care system. Therefore, worldwide efforts are being made to autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Gait rehabilitation requires the retraining of the nervous system and kinematics to reduce the stress applied to the musculoskeletal system [14]. Several studies of robot training have found that repetitive and intensive training after neurological injury is effective because it strengthens neural connections through task‐specific practice [15].…”
Section: Discussionmentioning
confidence: 99%
“…Gait rehabilitation requires the retraining of the nervous system and kinematics to reduce the stress applied to the musculoskeletal system [14]. Several studies of robot training have found that repetitive and intensive training after neurological injury is effective because it strengthens neural connections through task‐specific practice [15].…”
Section: Discussionmentioning
confidence: 99%
“…Body Weight Support BWS is a mechanical system used to help the patient carry some or the full weight of their body during standing [99], [100]. it provides stability to the trunk and the pelvis during movement, so that the patient performs gait training safely.…”
Section: A)mentioning
confidence: 99%
“…In the US, more than 700,000 people suffer from stroke, 10,000 suffer from traumatic, spinal cord injury, and 250,000 become disabled due to multiple sclerosis each year [1]. These injuries and diseases leave patients with greatly impaired or completely non-existent muscle function over time, making life for them increasingly more difficult.…”
Section: Introductionmentioning
confidence: 99%